Structural Deformation-Based Computational Method for Static Aeroelasticity of High-Aspect-Ratio Wing Model in Pressurized Wind Tunnel (Advances in Applied Mathematics and Mechanics, 2018)
In this study, the structural model of a high-aspect-ratio wing is unknownbut its structural deformation is measured at some attack angles in a pressured windtunnel. To implement the static aeroelastic computation at an arbitrary state, an inversionmethod is proposed to derive the structural stiffness from the known deformation.The wing is simplified into a single-beam model and its bending and torsional flexibilitydistributions are respectively expressed as a linear combination of several selectedbasis functions. The bending deformation can be then expressed as a linear combinationof the bending deformations of the models structurally characterized by each basisfunction, which are gradually evaluated by loading the aerodynamic loads computedat the chosen design state. Based on the measured deformation, the bending stiffnessdistribution is ultimately fitted by a least square method. The torsional stiffnessdistribution is solved in the same way. Resultantly, a structural deformation-basedcomputational method for static aeroelasticity of a high-aspect-ratio wing model isachieved by combining the structural stiffness inversion method with a coupled computationalfluid dynamics (CFD)-computational structural dynamics (CSD) algorithm.The present method is applied to the design and validation states and the numericalresults agree well with the experimental data.